2014
DOI: 10.5694/mja13.10875
|View full text |Cite
|
Sign up to set email alerts
|

High chlamydia positivity rates in Indigenous people attending Australian sexual health services

Abstract: The high and increasing chlamydia positivity rates highlight the need for enhanced prevention and screening programs for Indigenous people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 17 publications
2
9
0
Order By: Relevance
“…Similar findings have been reported overseas; a meta‐analysis of data from 35 studies found that indigenous women had elevated risks of invasive cervical cancer and related mortality (pooled risk ratios, 1.72 and 3.45 respectively) 13 . Indigenous Australians experience poorer outcomes than non‐Indigenous people for a range of conditions, 14 including some sexually transmissible infections (STIs) 15 . ‐ 17 In response to these inequities, the Australian Government initiated the Closing the Gap program in 2008, 18 followed in 2014 by the Fourth National Aboriginal and Torres Strait Islander Blood‐borne Viruses and STI Strategy, 2014–2017, which includes the aim of achieving high rates of HPV vaccination 19…”
supporting
confidence: 54%
“…Similar findings have been reported overseas; a meta‐analysis of data from 35 studies found that indigenous women had elevated risks of invasive cervical cancer and related mortality (pooled risk ratios, 1.72 and 3.45 respectively) 13 . Indigenous Australians experience poorer outcomes than non‐Indigenous people for a range of conditions, 14 including some sexually transmissible infections (STIs) 15 . ‐ 17 In response to these inequities, the Australian Government initiated the Closing the Gap program in 2008, 18 followed in 2014 by the Fourth National Aboriginal and Torres Strait Islander Blood‐borne Viruses and STI Strategy, 2014–2017, which includes the aim of achieving high rates of HPV vaccination 19…”
supporting
confidence: 54%
“…5,6 In Australia, these access issues are magnified for young people from low socioeconomic backgrounds and those living in non-urban areas. [10][11][12][13][14] Few studies have asked young people how they access health care services and how they assess the quality of such services, especially in relation to sexual and reproductive health (SRH) care. [10][11][12][13][14] Few studies have asked young people how they access health care services and how they assess the quality of such services, especially in relation to sexual and reproductive health (SRH) care.…”
Section: Introductionmentioning
confidence: 99%
“…Biddle recommends taking the most efficient approach possible to data collection and analysis in order to minimise participant burden. 180 In summary, research data published in the last five years and indexed on PubMed, 107 Aboriginal health liaison 8,041 b No O'Connor et al 115 Chlamydia 7,103 b Yes Dutton et al 170 Health 128 Albuminuria 860 No Lopez et al 114 Ischaemic heart disease 833 b Yes Hopkins et al 105 Psychological resilience 677 No Arjunan et al 106 Tobacco use 663 No Jamieson et al 164 Oral 113 Stressful events in children 344 b No Lalla et al 103 Oral mucosal disease 342 No Radford et al 104 Dementia 336 No Whish-Wilson et al 99 Birth outcomes 301 Yes Roberts-Thomson et al 117 Oral health 251 No Dorrington et al 174 Pap smears 213 No Gardener et al 102 Children 205 No Wong et al 126 Midwifery 177 Infant health 175 Yes Luke et al 181 Suicidal 169 Breast feeding 159 Yes Webster et al (Gudaga study) 166 Child growth 157 No Scott et al 110 Sexual health 155 No Miller et al (Gudaga study) 118 Child language assessment 150 No Arrow 100 Oral …”
Section: Sparse Research In Urban Populationsmentioning
confidence: 99%
“…However, the IIHS computerised HA Aboriginal and Torres Strait Islander peoples living in urban areas recruited more than 945 patients. Three of these four studies also used routinely collected clinical data, 107,115,170 and the fourth study 119 was based on national health survey data.…”
Section: Sampling and Computerised Health Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation